2022
DOI: 10.1177/07334648221146252
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Healthcare Workers in Long-Term Care during COVID-19: A Scoping Review

Abstract: Background: Although healthcare workers (HCWs) in long-term care (LTC) have experienced significant emotional and psychological distress throughout the pandemic, little is known about their unique experiences. Objective: This scoping review synthesizes existing research on the experiences of HCWs in LTC during the COVID-19 pandemic. Method: Following Arksey and O’Malley’s framework, data published between March 2020 to June 2022, were extracted from six databases. Results: Among 3808 articles screened, 40 arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 81 publications
3
19
0
Order By: Relevance
“…During the COVID-19 pandemic, healthcare workers have been shown to be affected in different contexts such as individual, interpersonal, institutional, social and political (Chemali et al, 2022). It is stated that in this period mental wellbeing of HCWs was affected and certain experiences can have devastating effects on both the personal and professional lives of healthcare workers (Boamah et al, 2023; Byrne et al, 2023; Chemali et al, 2022; van den Broek et al, 2023). From this point of view, the fact that HCWs increase alcohol and cigarette use for relaxation and socialization is a finding that should be emphasized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the COVID-19 pandemic, healthcare workers have been shown to be affected in different contexts such as individual, interpersonal, institutional, social and political (Chemali et al, 2022). It is stated that in this period mental wellbeing of HCWs was affected and certain experiences can have devastating effects on both the personal and professional lives of healthcare workers (Boamah et al, 2023; Byrne et al, 2023; Chemali et al, 2022; van den Broek et al, 2023). From this point of view, the fact that HCWs increase alcohol and cigarette use for relaxation and socialization is a finding that should be emphasized.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has also been shown that the increase in COVID-19 risk perceptions of healthcare workers statistically increased their death anxiety decreased their life satisfaction and psychological well-being (Özer et al, 2023). Moreover, it has been shown that this infection has a particular negative impact on the well-being of healthcare workers (Boamah et al, 2023; Byrne et al, 2023; Chemali et al, 2022; van den Broek et al, 2023; Wańkowicz et al, 2020). During the COVID-19 pandemic, healthcare workers have been shown to experience many negative conditions such as physical fatigue, anxiety, insomnia, and psychological distress (Diomidous, 2020; García-Martín et al, 2020; Labrague, 2021; Sagherian et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Staff who were not initially prepared to work in the ICU had to provide support to the regular ICU staff during this challenging period (Ludvigsson, 2020). Studies conducted during the pandemic have shown increased workloads, elevated levels of job‐related stress, and low job satisfaction among staff, including RNs working in hospitals (Makowicz et al., 2022), as well as among nursing staff in RCFs (Boamah et al., 2023). That said, studies also reveal that opportunities for professional development among RNs emerged, including leadership for nurses and better teamwork among health professionals (Melnikov et al., 2022; Sarabia‐Cobo et al., 2021).…”
Section: Background/rationalementioning
confidence: 99%
“…The COVID-19 pandemic has put tremendous strain on the US nursing home workforce . Burnout, low wages, poor work conditions, and the increased burden of caring for vulnerable residents during a health crisis have contributed to a 13.3% decrease in nursing home sector employment since the start of the pandemic . Nursing homes currently employ 1.37 million workers (roughly 10% below projected demand) and continue to face staff shortages .…”
Section: Introductionmentioning
confidence: 99%